2015
DOI: 10.18632/oncotarget.5159
|View full text |Cite
|
Sign up to set email alerts
|

BCAT1 expression associates with ovarian cancer progression: possible implications in altered disease metabolism

Abstract: Previously, we have identified the branched chain amino-acid transaminase 1 (BCAT1) gene as notably hypomethylated in low-malignant potential (LMP) and high-grade (HG) serous epithelial ovarian tumors, compared to normal ovarian tissues. Here we show that BCAT1 is strongly overexpressed in both LMP and HG serous epithelial ovarian tumors, which probably correlates with its hypomethylated status. Knockdown of the BCAT1 expression in epithelial ovarian cancer (EOC) cells led to sharp decrease of cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 98 publications
4
88
0
Order By: Relevance
“…BCAAs degradation is regulated by the BCAT1 and BCAT2 enzymes [34]. We have recently shown that the suppression of the BCAT1 gene in EOC cells resulted in the down-regulation of numerous genes implicated in lipid production and protein synthesis, suggesting its important role in controlling EOC metabolism [56]. Our data suggest a similar effect imposed by the suppression of the GALNT3 gene.…”
Section: Discussionsupporting
confidence: 60%
“…BCAAs degradation is regulated by the BCAT1 and BCAT2 enzymes [34]. We have recently shown that the suppression of the BCAT1 gene in EOC cells resulted in the down-regulation of numerous genes implicated in lipid production and protein synthesis, suggesting its important role in controlling EOC metabolism [56]. Our data suggest a similar effect imposed by the suppression of the GALNT3 gene.…”
Section: Discussionsupporting
confidence: 60%
“…For example, GPNMB/OA increases the invasiveness of human metastatic prostate cancer cell lines DU145 and PC3 through MMP2 and MMP9 activities, and also enhances tumorigenesis of human lung cancer and breast cancer PRRX1 promotes epithelial‐mesenchymal transition (EMT) through the Wnt/b‐catenin pathway in gastric cancer and also has been identified as a new EMT inducer in breast and colorectal cancer . Similarly, overexpression of BCAT1 , a c‐Myc target gene might associate with ovarian cancer progression and induce cell proliferation, migration and invasion in nasopharyngeal carcinoma . Some in vitro trials indicated that suppression of BCAT1 could significantly decrease tumour proliferation in glioma cell lines .…”
Section: Discussionmentioning
confidence: 99%
“…The cell lines were passed in different culture media supplemented with 10% fetal bovine serum, as described previously. 65,67 Bisulfite sequencing PCR (BSP) analysis BSP analysis was performed, as described previously. 65,67 Briefly, genomic DNA extracted from EOC tumors and control ovarian tissues was isolated using the Qiagen DNeasy Blood and Tissue Kit.…”
Section: Cell Culturesmentioning
confidence: 99%